2014
DOI: 10.3221/igf-esis.29.32
|View full text |Cite
|
Sign up to set email alerts
|

Development of biodegradable magnesium alloy stents with coating

Abstract: Biodegradable stents are attracting the attention of many researchers in biomedical and materials research fields since they can absolve their specific function for the expected period of time and then gradually disappear. This feature allows avoiding the risk of long-term complications such as restenosis or mechanical instability of the device when the vessel grows in size in pediatric patients. Up to now biodegradable stents made of polymers or magnesium alloys have been proposed. However, both the solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Bartosch et al concluded that the use of Mg stents is safe but the research on Mg stents should be expanded to large stent designs for large vessels and applications other than just coronary stents . There are a number of studies on the mechanical and degradation analysis of Mg‐based stents which will be discussed in detail in the “Computational Models” section.…”
Section: Current Biomedical Applications Of Mgmentioning
confidence: 99%
“…Bartosch et al concluded that the use of Mg stents is safe but the research on Mg stents should be expanded to large stent designs for large vessels and applications other than just coronary stents . There are a number of studies on the mechanical and degradation analysis of Mg‐based stents which will be discussed in detail in the “Computational Models” section.…”
Section: Current Biomedical Applications Of Mgmentioning
confidence: 99%
“…Most research was done on established materials like WE43, AZ31 or modifications of such alloys. Different magnesium alloys, surface modifications and coatings with or without anti‐proliferative substances have been analyzed in vitro as well as in vivo . Recently, Biotronik achieved CE‐marking for their degradable coronary stent “Magmaris.”…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid bioresorbable stents (HBSs), like magnesium alloy stents coated with a degradable polymer, are a very promising solution for coronary artery diseases. 1,2 The magnesium alloy substrate will be resorbed by the body after they have completed their function, 3 limiting long term complications related to the body inflammatory response caused by permanent implants. Furthermore, the polymer coating can improve the desired degradation kinetics, ensuring a protective action from the corrosive environment which can cause too fast degradation of stent substrates.…”
Section: Introductionmentioning
confidence: 99%